The history of the study of the red marmot (Marmota caudata Geoff., 1842) population in the western part of the Talas Alatau - Токарський, В. А. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
The detailed analysis of the literature data of XX–XXI centuries concerning the population status of the red marmot on the territory of the Aksu-Zhabagly Nature Reserve has been conducted. Marmots’ settlements concentrate exclusively in the highlands (zhailau) in the belt of alpine steppes and high sub-alpine, at an altitude of 2000–3000 meters above sea level and are confined to streams, outputs of groundwater and snowfields where the animals during the season are provided by a grassy juicy food. To date, marmot area has patchy character with mosaic and belt type of settlements. The area of 1800 hectares is inhabited by 102 families (about 320–330 individuals). Plots from 0.5 to 2 km2 are relatively isolated from each other with a density of 0.06 families for hectare. Thus, 22,700 individuals of the red marmot are suggested to be the real number in the territory of Aksu-Zhabagly Nature Reserve. This number describes the core of Kazakhstan’s population. The obtained data can serve as a starting point for objective forecasting of marmot population in the existing natural settlements.